(untitled) (Analysis in Theory and Applications, 2012)
In this paper, we will discuss the behavior of a class of rough fractional integral operators on variable exponent Lebesgue spaces, and establish their boundedness from L^p_1(·)(R^n) to L^p_2(·)(R^n).